PENINGKATAN KUALITAS DAN MINIMASI WASTE PADA PRODUKSI KAWAT TEMBAGA DENGAN METODE LEAN SIX SIGMA - Karuna, Rio; Kristina, Helena Juliana; Sukania, I Wayan (Universitas Tarumanagara, 2023)
The company where the research was conducted in 2014 located in Java Island, this company is engaged in the production of copper wire as a raw material for copper cables. The company experienced major problems, namely high transportation and production costs, as well as waiting time due to repairing defective products. This is because the quality control process of raw materials has not been effective in detecting the cause of defective products. In this study, it used the lean six sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach to minimize waste and improve the quality of copper wire measuring 2.8 mm. After anlysis and data processing, the percentage of defect waste was 28.98%, waiting waste was 22.91%, and overprocessing waste was 18.87%. Meanwhile, the DPMO value was 6539 and the sigma value was 3.98. In the PCE calculation to find out the value of the efficiency of the production process, a value of 39.72% was obtained. After various kinds of analysis are carried out to find out the root cause of the problem, corrective actions are carried out in accordance with the cause of the existing problem. The result of this research for the company is the provision of proposed improvements in the form of making one-point lessons and checksheets to reduce the production of defective goods.